Prosthetics and Orthotics - Arazpour, Mokhtar (IntechOpen, 2021)
This book consists of two parts: Prosthetics and Orthotics. Over the years there has been rapid development in prostheses and orthoses. Advancement of technology, significant progress in computer components and robotics, and the development of new materials have enabled many people in need to return to useful and practical life. This book provides information for effective clinical decision-making for those working with people who need medical supportive devices. Over two parts, chapters in this volume examine construction methods, applications, and effects of prosthetic and orthotic devices.